2013
DOI: 10.1371/journal.pone.0053106
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Monocyte Sirt1 Expression Is Reduced in Patients with Coronary Artery Disease

Abstract: BackgroundInflammation plays a key role in atherosclerosis. Sirt1 regulates transcription factors involved in inflammatory processes and blunts atherosclerosis in mice. However, its role in humans remains to be defined. This study was therefore designed to investigate the role of Sirt1 in the development of atherosclerosis.Methods and Results48 male subjects admitted for cardiac catheterization were subdivided into healthy subjects, patients with stable coronary artery disease (CAD), and with acute coronary sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 19 publications
2
39
1
Order By: Relevance
“…It has also been reported that the blood levels of SIRT1 proteins are increased in patients suffering from cardiovascular disease (CVD) compared to that noted in healthy subjects 23) . These observations conflict with the results of our studies of ACS and another study of coronary artery disease 7) . In addition, we compared the mRNA expression levels of the SIRT1 gene in the AMI and UA patients and found that the SIRT1 expression levels were lower in the AMI patients than in the UA patients.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…It has also been reported that the blood levels of SIRT1 proteins are increased in patients suffering from cardiovascular disease (CVD) compared to that noted in healthy subjects 23) . These observations conflict with the results of our studies of ACS and another study of coronary artery disease 7) . In addition, we compared the mRNA expression levels of the SIRT1 gene in the AMI and UA patients and found that the SIRT1 expression levels were lower in the AMI patients than in the UA patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Our case-control study using gene expression microarrays and real-time PCR replication demonstrated that the SIRT1 mRNA expression level is associated with ACS, with a decreased expression in the PBMCs of the ACS patients, while earlier studies of the SIRT1 gene expression reported a reduced expression of the SIRT1 gene in monocytes derived from ACS patients 7) . PBMCs and monocytes are both cells related to the pathogenesis of ACS.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…Research data indicated that monocytic SIRT1 expression is reduced in patients with stable coronary artery disease and acute coronary syndromes. 80 Moreover, SIRT1 plays an important role in the prevention of atherosclerosis. Zeng and colleagues 81 reported that SIRT1 may prevent the formation and progression of atherosclerosis by enhancing the liver X receptor-ATP-binding cassette, A1/ABCG1/C-C chemokine receptor type 7, and inhibiting the NF-κB pathways.…”
Section: The Role Of Sirt1 In Human Heart Diseasesmentioning
confidence: 99%